SINERGITAS DAN KOLABORASI TERHADAP PEMBANGUNAN DESA MELALUI PROGRAM KULIAH KERJA NYATA DI KABUPATEN BEKASI - Nurhidayah, Siti; Basri, Hasan; Putrianika, Puput; Desty Widyowati, Dian (LPPM Universitas Islam 45 Bekasi, 2024)
Kuliah Kerja Nyata (KKN) is an education where students have the opportunity to learn in a community setting. KKN helps students discover potential and address problems so that they can build on the potential of the village or area and find solutions to existing problems in the village. The problem analysis obtained through the Bekasi Regency BAPPEDA institution is that the high stunting rate and the behaviour patterns of people who are accustomed to open defecation are still common in the Cabangbungin and Pebayuran sub-districts of Bekasi Regency. The purpose of KKN service is to improve the welfare of village communities in contributing to building creative and innovative villages in the field of business and entrepreneurship in accordance with the Vision of the Government of West Java Juara, Mandiri, Maju, and Sejahtera. The KKN service method of applying community education and mentoring with target participants is relevant. Overall, the service programme through KKN helps the community understand the importance of good sanitation and a healthy diet to prevent stunting, get the changes needed for regional development, and build development cadres in the community to ensure continued village development.